(untitled) (International Journal of Nursing Education, 2020)
Introduction: During pregnancy many changes occur in women’s self-concept and the changes in their selfimage and the shift in focus from themselves to the needs of the foetus and unfamiliar territory of pregnancy and early motherhood creates anxiety. Relaxation techniques are a great way to help in managing anxiety such as progressive muscle relaxation technique(PMRT) which may be very useful for treating anxiety symptoms during pregnancy. Aim: The aim of this study is to assess the effect of progressive muscle relaxation on anxiety among antenatal mothers. Material & Method: Quasi Experimental design with two group pre-test and post-test design was used. Conceptual framework for the study was adopted from Ludwig Von Bertalanffy (1968) General System Model was chosen to conduct the study. Through convenience sampling, 35 subjects were selected in experimental and 35 in control group. Subjects in experimental group (n=35) were provided PMRT and conventional care and in control group (n=35) only conventional care was provided. Perinatal Anxiety Screening Scale (PASS) and Socio demographic data sheet was used to collect the data. Results: Results revealed that there was significant difference in level of anxiety after four weeks of progressive muscle relaxation technique in experimental group (p value 0.005) as compared to control group. However, there was no association of pre-test level of anxiety with selected demographic variables Conclusion: The study concluded that progressive muscle relaxation technique was effective in reducing anxiety among antenatal mothers after 4 weeks of intervention in experimental group